PENGARUH KUALITAS PRODUK, KEPERCAYAAN, KEAMANAN, HARGA, KEMUDAHAN, PROMOSI, TERHADAP KEPUASAN KONSUMEN DALAM MELAKUKAN PEMBELIAN TERHADAP E-COMMERCE SHOPEE - Nurhidayat, Maulana Furqon; Komara, Edi; Rofianto , Whony; Rimadias, Santi (Journal of Accounting, Management and Islamic Economics, 2024)
The Influence of Product Quality, Security, Trust, Price, Ease of Use, and Promotion on Consumer Satisfaction in Making Purchases on the E-commerce Platform Shopee." The independent variables in this research are product quality, security, trust, price, ease of use, and promotion, while the dependent variable is consumer satisfaction. The hypothesis testing in this study uses PLS or Partial Least Square with the SmartPLS 3.0 software. The data collection technique involves using a Google Form questionnaire to gather information from respondents. The sample in this study consists of 150 respondents from various groups who use the Shopee e-commerce platform. The analysis results show that product quality does not have a positive and significant effect on consumer satisfaction, security does not have a positive and significant effect on consumer satisfaction, trust does not have a positive and significant effect on consumer satisfaction, price has a positive and significant effect on customer satisfaction, ease of use does not have a positive and significant effect on consumer satisfaction, and promotion does not have a positive and significant effect on consumer satisfaction.